Two high-pressure phases of SiS2 as missing links between the extremes of only edge-sharing and only corner-sharing tetrahedra - Evers, Jürgen; Mayer, Peter; Möckl, Leonhard; Oehlinger, Gilbert; Köppe, Ralf; Schnöckel, Hansgeorg (Inorganic Chemistry, 2015)
The ambient pressure phase of silicon disulfide (NP-SiS2), published in 1935, is orthorhombic and contains chains of distorted, edge-sharing SiS4 tetrahedra. The first high pressure phase, HP3-SiS2, published in 1965 and quenchable to ambient conditions, is tetragonal and contains distorted corner-sharing SiS4 tetrahedra. Here, we report on the crystal structures of two monoclinic phases, HP1-SiS2 and HP2-SiS2, which can be considered as missing links between the orthorhombic and the tetragonal phase. Both monoclinic phases contain edge- as well as corner-sharing SiS4 tetrahedra. With increasing pressure, the volume contraction (V/V) and the density, compared to the orthorhombic NP-phase, increase from only edge-sharing tetrahedra to only corner-sharing tetrahedra. The lattice and the positional parameters of NP-SiS2, HP1-SiS2, HP2-SiS2, and HP3-SiS2 were derived in good agreement with the experimental data from group-subgroup relationships with the CaF2 structure as aristotype. In addition, the Raman spectra of SiS2 show that the most intense bands of the new phases HP1-SiS2 and HP2-SiS2 (408 and 404 cm-1, respectively) lie between those of NP-SiS2 (434 cm-1) and HP3-SiS2 (324 cm-1). Density functional theory (DFT) calculations confirm these observations.
CRIS-Team Scopus Importer:2024-09-09